PENGARUH KELOMPOK TEMAN SEBAYA TERHADAP PERILAKU INTERAKSI SOSIAL SISWA MTS NURUS SALAM DELI TUA - Sari, Vivi Artika; Hutasuhut, Dina Hidayati; Syaimi, Khairani Ulfa; Dewi, Ika Sandra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the influence of peer groups on students' social interaction behavior at MTs Nurus Salam Deli Tua. Adolescence is an important developmental stage in an individual's life, where interaction with peers plays a significant role in shaping social behavior. This study used a quantitative approach with a simple linear regression method. The sample consisted of 45 students selected through random sampling techniques from a total population of 177 students. Data were collected using a questionnaire that had been tested for validity and reliability. The results of the validity test showed that most of the statement items in the questionnaire on social interaction behavior and peer groups had an r-table value (0.2500), which means it was valid and suitable for use in research. The results of the reliability test also showed that the instrument used had a high level of consistency with a reliability coefficient value included in the reliable category. Furthermore, the results of the regression analysis showed that there was a significant relationship between peer groups and students' social interaction behavior. The regression test produced a significant value of 0.008 <0.05, which indicated that peer groups had a positive and significant influence on social interaction behavior. The better the peer influence, the better the students' social interaction behavior. These findings are expected to serve as a reference for schools, guidance counselors, and parents in fostering students' social development.